Understanding Confucianism - "Moore, Jennifer Oldstone" (London, 2003)
A wonderful insight into the development of Confucianism as it traces its existence from ancient China to the modern day. Confucianism has made a significant contribution to the moral, philosophical and spiritual history of humankind. For more than two thousand years, its ethical code - with its firm emphasis on the family, social order and self-discipline - has sustained Chinese civilization and shaped the people and history of East Asia. Today, the teachings of Confucius offers insight into values of community and mutual responsibility so often lacking in the modern world. This concise, illustrated volume is an accessible introduction to the key themes of Confucianism - the life of Confucius and his teachings, ritual and ceremony, art and architecture, sacred writings, death and the afterlife, the state, the family and the individual. Providing a unique distillation of this ancient and compelling tradition, the book traces the course of Confucianism, from its origins in ancient China to its place in society today.
Keywords: Religion